KEOTONOMIAN SASTRA DALAM NOVEL ASMARALOKA KARYA DANARTO - Agus Yulianto (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2017)
The aim of this research was to know the form or model of literature autonomy in the novel Asmaraloka by Danarto. It discussed about the literature autonomy form or model of this novel. It was qualitative descriptive and used literature review. Based on the analysis, the literature autonomy in Asmaraloka was shown in the author’s independency in creating chronic, that was plotting which was in general contradicting the reality and the story background which represented strong literature autonomy.